Relationship between the anthocyanin content values in the leaf sheath base of barley cultivars and in the grain of the hybrids derived from them - O. Yu. Shoeva; T. V. Kukoeva (Труды по прикладной ботанике, генетике и селекции)
Background. The development of barley cultivars accumulating anthocyanins in grain is an important task for breeding, which is based on the Ant1 and Ant2 genes that control synthesis of these compounds. To optimize the breeding strategy and selection of the initial material, quantitative assay of anthocyanin content in the leaf sheath base of barley cultivars was carried out and the relationship between this parameter for some of the barley cultivars and anthocyanin content in grain of the hybrids derived from them was evaluated.Materials and methods. The anthocyanin content in the leaf sheath base was studied in 32 barley cultivars in the tillering stage and in mature grains of 11 purple-grain hybrids selected from the hybrid populations using DNA-markers.Results and discussion. It was shown that there were quantitative differences in the anthocyanin content in the leaf sheath base among barley cultivars, which varied from 1 to 191 mg/kg. A cluster analysis helped to identify three groups of cultivars: with low, medium and high anthocyanin content. The hybrids from crossing cultivars differing in their anthocyanin content in the leaf sheath base with line P18, the donor of the dominant allele of the Ant2 gene, showed variation of the anthocyanin content in grain from 22 to 71 mg/kg. The observed differences among the hybrids were determined by the genotypes of individual plants and the allelic state of Ant2. A weak correlation (rs = 0.37, p = 0.0362) was shown between the anthocyanin contents in the leaf sheath base and in the grain of the obtained hybrids.Conclusion. The results of the study would help to optimize the breeding strategy for the development of new barley cultivars with high anthocyanin content in the grain and substantiate the need to test the anthocyanin content in the grain of individual lines.